HUBUNGAN ANTARA TEKHNIK MENYUSUI YANG TIDAK BENAR DENGAN KEJADIAN BENDUNGAN ASI PADA IBU NIFAS - Tuti Meihartati (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Immunization is a deliberate attempt was made to provide immunity to the baby in order to avoid certain diseases in accordance with the type of wide immunizations given. Ideally babies get 9 types of basic immunizations before 1 year old in order to complete immunization. However, not a few babies who do not achieve a complete basic immunization for various reasons. One of the factors that most contribute to the completeness of basic immunization is the mother's behavior. Mothers’ good behavior would seek her children receive complete primary immunization on the contrary. This study aims to see whether there is correlation between the mother’s behavior with their infant basic immunization. The study was conducted Puskesmas Bungkukan Kecamatan Kelumpang Barat Kabupaten Kotabaru. The choice of location of this study is based on the consideration that there are many infants who have not been immunized. In 2014 there are 70.96% of infants aged 0-11 months were immunized. While EPI (Expanded Programme on Immunization) has set the immunization coverage should reach the target of 80%. This study method was analytical survey. The study design by using cross sectional. The data of study was obtained from the primary data in Puskesmas Bungkukan. The sampling technique was quota sampling. This study was conducted in Puskesmas Bungkukan on April to June in 2015. The results of statistical test was chi-square obtained p-value of 0.000 <α = 0,05 thus Ho was rejected and Ha was accepted. The result of this study proves that there was correlation between the mother’s behavior with complete basic immunization. Conclusions of this study showed that there is a relationship between the behavior of mothers with complete basic immunization in infants aged 11 months in the working area Puskesmas Bungkukan. Based on these results, it was important to be pursued in order to good mother's behavior, such as providing knowledge, awareness and motivation to the mothers about the benefits of immunization.